ANALYSIS OF STUDENT LEARNING STYLES IN THE CLASSROM AT ELEMETARY SCHOOL - Hidayati, Nia; Triyogo, Agus (LP3MKIL, 2023)
This research is motivated by the learning achievement in social studies subjects at SD Negri 46 Lubuklinggau which can be categorized as less, compared to other subjects. This is because the learning process in the classroom does not make students interested in the teaching style applied by the teacher. This study aims: To determine the form of visual, auditory and kinaesthetic learning styles of students in developing student achievement in social studies subjects. The design in this study the researcher used a qualitative approach with data collection methods in the form of interviews, observation and documentation. This research was conducted at SD Negri 46 Lubuklinggau with 32 students as the subject of research. visual learning style are 20 students, students who tend to have an auditory learning style are 20 students. 6 students, while there are 6 students who tend to have a kinaesthetic learning style. Keyword: learning style, students, classroom, elementary school